La mobilité internationale des ressources humaines hautement qualifiées au Mexique face à la crise économique internationale - Sylvie Didou-Aupetit (Les éditions de la Maison des sciences de l'Homme, 2010)
In this paper, we will try to evaluate some recent trends, characteristics of highly skilled migrants, mainly doctorate recipients, between Mexico and OECD geographical zone, in the framework of a massive migration. We will analyze the elements of public policies which had have positive repercussions on student and professional mobility, taking into account the current state of the debate and the knowledge on brain drain. We will track finally the impacts of economic crisis of 2008 on the returns to origin country of university alumni and graduates and on the international academic networks "organization".